2021
DOI: 10.3390/ani11010092
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Seafood Preservation Technologies: Recent Developments

Abstract: Fish and fishery products are among the food commodities of high commercial value, high-quality protein content, vitamins, minerals and unsaturated fatty acids, which are beneficial to health. However, seafood products are highly perishable and thus require proper processing to maintain their quality and safety. On the other hand, consumers, nowadays, demand fresh or fresh-like, minimally processed fishery products that do not alter their natural quality attributes. The present article reviews the results of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 217 publications
0
22
0
Order By: Relevance
“…Avocado seed extracts prevented an increase in the redness and yellowness of shrimp muscle during storage [ 28 ]. Use of a COSP coating had no important effect on yellowness but did increase lightness and redness for coated cod patties [ 29 ]. The a* value was correlated with the TVC of microbial species ( R 2 = 0.98, 0.94, 0.91, 0.95, and 0.97) in the control and 0.5%, 1.0%, 2.0%, and 4.0% COSP-treated shrimp, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Avocado seed extracts prevented an increase in the redness and yellowness of shrimp muscle during storage [ 28 ]. Use of a COSP coating had no important effect on yellowness but did increase lightness and redness for coated cod patties [ 29 ]. The a* value was correlated with the TVC of microbial species ( R 2 = 0.98, 0.94, 0.91, 0.95, and 0.97) in the control and 0.5%, 1.0%, 2.0%, and 4.0% COSP-treated shrimp, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, raw materials, processing technologies, storage conditions, enzymes of fish, and microflora are mainly responsible for fresh fish unacceptability [ 18 ]. Even though various preservation strategies are proposed in the literature to preserve seafood products [ 19 , 20 , 21 ], the most diffused approach for fresh fish burgers is based on the adoption of natural compounds, properly encapsulated or combined with modified atmosphere conditions [ 16 , 17 , 22 , 23 , 24 ] or enclosed in edible films [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11][12] In previous reports, edible coatings based on polysaccharides such as chitosan, alginate, pectin, and pullulan (PUL), as well as proteins such as gelatin, soy protein isolate, whey protein isolate, wheat gluten, and collagen, have been applied to preserve a variety of sh and shery products. 4,13 Furthermore, nisin, 3-polylysine (PL), lactoperoxidase, plant extracts (e.g., grape seed extract, tea polyphenols and licorice extract) as well as various essential oils, all with antimicrobial and antioxidative properties, have been used to prepare edible coatings for sh. 2,4,13 The results from these reports showed that use of edible coatings successfully maintained sh quality and resulted in an extension of product shelf-life.…”
Section: Introductionmentioning
confidence: 99%
“…4,13 Furthermore, nisin, 3-polylysine (PL), lactoperoxidase, plant extracts (e.g., grape seed extract, tea polyphenols and licorice extract) as well as various essential oils, all with antimicrobial and antioxidative properties, have been used to prepare edible coatings for sh. 2,4,13 The results from these reports showed that use of edible coatings successfully maintained sh quality and resulted in an extension of product shelf-life.…”
Section: Introductionmentioning
confidence: 99%